Clinical-epidemiological characteristics of tuberculose and HIV coinfection in the State of Piauí, Brazil (Research, Society and Development, 2020)
Objective: To trace the epidemiological profile and clinical characteristics of tuberculosis infection in HIV-positive patients in Piauí. Methodology: This is an epidemiological, quantitative and descriptive study, based on the data collected in the Information System for Notifiable Diseases (SINAN) in Piauí, on TB/HIV co-infection between the period 2010 to 2019. We selected sociodemographic and clinical variables of the disease. The data were analyzed using simple descriptive statistics and presented in tables using absolute and relative frequencies. Results: 8,017 TB cases were reported, of which 546 had positive anti-HIV serology. The serological test was not performed in 2,507 (31.2%) of the reported cases. Cases of TB/HIV co-infection occurred predominantly in male individuals (77%), aged 20 to 39 years (56.4%), in the pulmonary clinical form (67.9%). Of the 422 patients who had an informed closure situation, the cure rate was 58.0%, 11.8% dropout, and 7.1% TB deaths. Conclusion: The study allowed to know the most prevalent epidemiological profile of the disease, evidencing the low rates of HIV serological investigation and cure, and high rates of dropouts and deaths in Piauí. It is necessary the provision of subsidies for directing new strategies for the prevention and control of TB/HIV co-infection in state health services.